Analysis of Factors of Sports Migration and the Effectiveness of Competitive Activity of Football Players - Sobol, E.; Doroshenko, I.; Svatyev, A.; Doroshenko, E. Yu.; Tsyganok, V. I.; Shamardin, V.; Соболь, Е.; Дорошенко, І.; Сватєв, А.; Дорошенко, Едуард Юрійович; Циганок, Владислав Іванович; Шамардін, В. (My University, 2024)
The purpose of the work: determine the ways of correcting the training process based on taking in to account the influence of sports migration factors on the training of highly qualified football players. Material and methods. To assess the impact of factors of sports migration on the effectiveness of competitive activity, the indicators of the competitive activity of football players of the national team of Ukraine in 16 official games during the 2020-2021 and 2021-2022 seasons. Methods of research. Analysis, generalization and systematization of data from scientific and methodological literary sources and the “Internet”, pedagogical observations, content analysis of competition regulations (based on the materials of the official FIFA; UEFA; UAF sites), analysis of performance indicators of competitive activity; method of expert evaluations; methods of mathematical statistics. Results. The 2020-2021 season: in 62,5% of official games, higher indicators were recorded for football players of the first group (“migrants” and “naturalized” athletes), the range of indicators – from 58.33% to 77.50%. At the same time, statistically significant differences (25.00%) were recorded in 2 games. In one game, higher indicators were recorded for football players of the first group (“migrants” and “naturalized” athletes) and, in one game, higher indicators were recorded for football players of the second group (athletes who were born in Ukraine are national athletes of the UAF and participate in UPL competitions). The 2021-2022 season: in 62.5% of official games, higher indicators were recorded for football players of the first group (“migrants” and “naturalized” athletes), the range of indicators – from 50.01% to 74.16%. No statistically significant differences were recorded. The comparative effectiveness of football players of the first and second groups was 46.15% and 53.85%, respectively. Conclusion. This state of affairs indicates the need to correct the modern system of multi-year improvement of highly qualified football players based on the development and formation of technologies for the direct training of migrant athletes for official international competitions. Мета роботи: визначити шляхи корекції тренувального процесу на основі врахування впливу факторів спортивної міграції на підготовку висококваліфікованих футболістів. Матеріал і методи. Для оцінки впливу чинників спортивної міграції на ефективність змагальної діяльності проаналізовано показники змагальної діяльності футболістів національної збірної команди України в 16 офіційних іграх протягом сезонів 2020-2021 та 2021-2022 років. Методи дослідження. Аналіз, узагальнення та систематизація даних науково-методичних літературних джерел та мережі «Інтернет», педагогічні спостереження, контент-аналіз регламентних документів змагань (за матеріалами офіційних сайтів ФІФА; УЄФА; УАФ), аналіз показників ефективності змагальної діяльності; метод експертних оцінок; методи математичної статистики. Результати. Сезон 2020-2021 рр.: у 62,5% офіційних ігор вищі показники зафіксовано у футболістів першої групи («мігранти» та «натуралізовані» спортсмени), діапазон показників – від 58,33% до 77,50%. При цьому статистично значущі відмінності (25,00%) були зафіксовані у 2 іграх. В одній грі вищі показники зафіксовано у футболістів першої групи («мігранти» та «натуралізовані» спортсмени) та, в одній грі, вищі показники зафіксовано у футболістів другої групи (спортсмени, які народилися в Україні, є національними спортсменами УАФ та беруть участь у змаганнях УПЛ). Сезон 2021-2022 рр.: у 62,5% офіційних ігор вищі показники зафіксовано у футболістів першої групи («мігранти» та «натуралізовані» спортсмени), діапазон показників – від 50,01% до 74,16%. Статистично значущих відмінностей не зафіксовано. Порівняльна ефективність футболістів першої та другої груп склала 46,15% та 53,85% відповідно. Висновок. Такий стан справ свідчить про необхідність корекції сучасної системи багаторічного вдосконалення висококваліфікованих футболістів на основі розробки та формування технологій безпосередньої підготовки спортсменів-мігрантів до офіційних міжнародних змагань.
Аналіз факторів спортивної міграції та ефективності змагальної діяльності футболістів
Doroshenko E. Yu. - https://orcid.org/0000-0001-7624-531X; Tsyganok V. I. - https://orcid.org/0000-0001-9124-8068;
Keywords: football; highly qualified athletes; sports migration; training; competitive activity; футбол; висококваліфіковані спортсмени; спортивна міграція; підготовка; змагальна діяльність